1990
DOI: 10.1530/acta.0.1220479
|View full text |Cite
|
Sign up to set email alerts
|

Renal calcium and magnesium handling in experimental diabetes mellitus in the rat

Abstract: Abstract. Metabolic and renal clearance techniques were used to examine kidney function in conscious and anesthetised streptozotocin diabetic rats. All diabetics showed an enhanced calcium and magnesium excretion compared to controls. However, the renal handling of these ions in relation to other electrolytes varied with different experiments. In non-infused conscious rats, the excretion of all ions was higher in diabetics, but the increased output of Ca2+ and Mg2+ was far greater than that of other electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 0 publications
7
38
4
Order By: Relevance
“…The results from these studies clearly indicate that diabetic animals have hypercalciuria, decreased circulating 1,25(OH)2D3, and reduced bone mass. While hypercalciuria occurs, plasma levels of ionized and total Ca 2+ can be maintained at normal levels in several study models [7][8][9]34]. These data implicate that a compensatory mechanism for diabetes-induced renal Ca 2+ loss exists.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results from these studies clearly indicate that diabetic animals have hypercalciuria, decreased circulating 1,25(OH)2D3, and reduced bone mass. While hypercalciuria occurs, plasma levels of ionized and total Ca 2+ can be maintained at normal levels in several study models [7][8][9]34]. These data implicate that a compensatory mechanism for diabetes-induced renal Ca 2+ loss exists.…”
Section: Discussionmentioning
confidence: 98%
“…Hypercalciuria is commonly associated with diabetes [4][5][6][7][8][9]. However, the number of studies addressing the pathophysiology of altered Ca 2+ homeostasis during diabetes [7][8][9]34] is limited. The results from these studies clearly indicate that diabetic animals have hypercalciuria, decreased circulating 1,25(OH)2D3, and reduced bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Low turnover osteopenia with reduced mineral content has also been well documented in experimental models of IDDM, such as streptozotocin-induced (Ishida et al 1988) and spontaneous rat diabetes (Verhaeghe et al 1989(Verhaeghe et al , 1990. Another prominent feature of human and experimental IDDM is an increased urinary excretion of calcium and magnesium (Raskin, Stevenson, Barilla & Pak, 1978;Anwana & Garland, 1990). Plasma calcium concentration in the rat is normally maintained in the face of such renal losses (Anwana & Garland, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Another prominent feature of human and experimental IDDM is an increased urinary excretion of calcium and magnesium (Raskin, Stevenson, Barilla & Pak, 1978;Anwana & Garland, 1990). Plasma calcium concentration in the rat is normally maintained in the face of such renal losses (Anwana & Garland, 1990). A decreased bone mineral content may therefore represent an I I Corresponding author: hgarland@ fs 1.scg.man.ac.uk unfortunate consequence of the marked hypercalciuria serving to maintain normocalcaemia under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The low levels are attributed to glucosuriarelated increased renal magnesium loss. 2,4 Hypomagnesaemia has been associated with decreased glucose disposal both in patients with Type 2 DM and in non-diabetic subjects. 5 Paolisso et al have shown that oral magnesium supplementation in patients with Type 2 DM and mildly decreased plasma magnesium levels improves insulin sensitivity and secretion.…”
Section: Introductionmentioning
confidence: 99%